Pengaruh Posisi Head Up 30 Derajat & Murottal Al-Qur’an Terhadap Saturasi Oksigen Pada Pasien CVA Di RSUD Soegiri Lamongan - Windy Desy Nawang Ningrum; Rizky Asta Pramestirini; Virgianti Nur Faridah (Jurnal Keperawatan Muhammadiyah, 2026)
Objective: The blood flow in patients with cerebrovascular accident(CVA) is impaired, causing hemodynamic disturbances includingdecreased oxygen saturation. This study aims to determine theeffect of the head-up 30-degree position and Murrotal Al-Qur’an onoxygen saturation in CVA patients at RSUD Soegiri Lamongan.Methods: The research design used a pre-experimental approachwith a one-group pre-test and post-test design. From a populationof 38 patients, samples were obtained using consecutive sampling.Oxygen saturation was measured using an oximeter for 30 minutesover 3 days according to Standard Operating Procedures (SOP).Data were analyzed using the Wilcoxon test.Results: Before the intervention, all 34 patients were classified ashaving abnormal oxygen saturation. After the intervention, 30patients showed increased oxygen saturation. The Wilcoxon testresults showed a significance value of p = 0.00, indicating asignificant effect of the intervention on increasing oxygensaturation.Conclusion: One alternative to increase oxygen saturation is thecombination of the head-up 30-degree position and Murrotal Al-Qur’an